Tantangan Hukum Dalam Pemberantasan Terorisme di Indonesia : Evaluasi dan Prospek ke Depan (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
Eradicating terrorism has become a top priority for the Indonesian government in maintaining security and peace in this country. However, these efforts are faced with complex legal challenges. This journal evaluates these challenges and formulates future prospects. Legal challenges include legislative aspects, law implementation, law enforcement, and human rights protection. One of the main challenges is the balance between the need for national security and the protection of human rights. Coordination between law enforcement, intelligence and other related agencies is also a challenge. The Indonesian government's efforts to overcome these challenges involve the establishment of special institutions and mechanisms, training of law enforcement personnel, as well as international cooperation in intelligence exchange and law enforcement. The research method uses a qualitative approach with a literature review of related information sources. Through descriptive analysis, this research explores legal regulations, policies and field practices related to eradicating terrorism in Indonesia. Evaluation of the efforts that have been made includes strengthening anti-terrorism laws, establishing special institutions and units, as well as international cooperation.